2004
DOI: 10.1038/sj.onc.1207986
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ATM and Chk2 kinases in relation to the amount of DNA strand breaks

Abstract: The diverse checkpoint responses to DNA damage may reflect differential sensitivities by molecular components of the damage-signalling network to the type and amount of lesions. Here, we determined the kinetics of activation of the checkpoint kinases ATM and Chk2 (the latter substrate of ATM) in relation to the initial yield of genomic DNA single-strand (SSBs) and double-strand breaks (DSBs). We show that doses of c-radiation (IR) as low as 0.25 Gy, which generate vast numbers of SSBs but only a few DSBs per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 60 publications
4
77
0
1
Order By: Relevance
“…In fact, the S-phase DNA damage checkpoint was reported to require a threshold level of damage to activate the checkpoint response (Shimada et al, 2002). Full activation of Chk2, an effector of the S-phase DNA damage checkpoint, was reported to require radiation doses above 2 Gy (Buscemi et al, 2004), indicating the presence of a threshold for the induction of the whole battery of S-phase DNA damage responses. Our data suggested that 1 Gy of gammairradiation is enough to activate p53 to execute the p53-dependent suppression of replication fork progression in MEFs through phosphorylation of PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the S-phase DNA damage checkpoint was reported to require a threshold level of damage to activate the checkpoint response (Shimada et al, 2002). Full activation of Chk2, an effector of the S-phase DNA damage checkpoint, was reported to require radiation doses above 2 Gy (Buscemi et al, 2004), indicating the presence of a threshold for the induction of the whole battery of S-phase DNA damage responses. Our data suggested that 1 Gy of gammairradiation is enough to activate p53 to execute the p53-dependent suppression of replication fork progression in MEFs through phosphorylation of PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins of the DDR are rapidly recruited to sites of breaks, leading to the formation of nuclear foci 22,23 that are cleared upon DNA repair. We enumerated g-H2AX foci in ihNSCs at D0 treated with 0.25 or 1 Gy IR and collected 5 and 60 min and 24 h later (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] In ATM-deficient cells, the phosphorylation of the ATM targets is markedly attenuated. 23 To determine the effect of ATM depletion in our cells, we analyzed the genotoxic response on western blots using antibodies specific for ATM phosphoresidues. At D0, a dose of IR as low as 0.5 Gy induced in shCon the phosphorylation of ATM-S1981 and of its substrates Smc1-S966, Chk2-T68 and p53-S15 (Figure 3), though this response was more vigorous with higher doses of IR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have indicated that ATM and CHK2 are specifically activated by drug (calicheamicin) or radiation-induced DNA double-strand breaks (DSBs), and the level of activation directly correlates to the number of DNA DSBs [58,59]. Our previous studies demonstrated that irofulven activates ATM and its targets, NBS1, SMC1, CHK2 and p53 [42].…”
Section: Discussionmentioning
confidence: 98%